Involvement of The Jemaah Ahmadiyah Indonesia (JAI) in Promoting “Peaceful Islam” Through The Website - Adeni; Silviatul Hasanah; Andi Faisal Bakti (Proceeding of Saizu International Conference on Transdisciplinary Religious Studies, 2021)
The existence of Jemaah Ahmadiyah Indonesia (JAI) is still considered controversial in Indonesia. However, this community seems to be voicing peaceful Islam through their official website media. By using a qualitative method based on a netnographic approach (online observation), several steps are taken, namely visiting the Ahmadiyah website at https://ahmadiyah.id/, entering the keyword “peaceful Islam (Islam Damai)” to select related articles, then classifying and analyzing the data. This paper concludes that Ahmadiyah is involved in promoting harmony in Indonesia amidst the issue of radicalism. What they do is adjust their views and movements to the principles of the state within the framework of the Unitary State of the Republic of Indonesia (NKRI). The peaceful Islam they promote can be seen from the narratives of the articles they post, such as Universal Islam, Islam and equality of human rights, Islam and the reinterpretation of jihad, Islam is not a religion of war (taking up arms, relations between Islam and non-Muslims, Islam and Europe civilization, Islam and love for all, hatred for none. The involvement of JAI in promoting harmony has become a counter-narrative against other communities that have cornered Ahmadiyah.